Which anthropometric and lower body power variables are predictive of professional and amateur playing status in male rugby union players?. Issue 1 (February 2019) - Jones, Thomas W; Keane, Karen; Smith, Andrew; Dent, Jack; McShane, Kevin; Payne, Tim; Williams, Lewis; Maguire, Phillip; Marshall, Steven J; Graham-Smith, Philip
The purpose of this study was to compare anthropometric and lower body power measurements between current professional and amateur male rugby union players. The present study also sought to determine which anthropometric and physical performance variables were predictive of playing standard. Thirty professional and 30 amateur RU players performed Wattbike 6 s maximal effort (WB6S) and countermovement (CMJ) and squat jump (SJ) assessments, anthropometric measures were also taken. Dependant variables recorded and analysed including: body mass, stature, Σ8 site skinfolds, WB6S absolute and relative peak power, CMJ and SJ average concentric force, jump height, peak velocity, time to peak force, rate of force development (RFD) and absolute and relative peak force and power. Professional players were heavier, taller and leaner than their amateur counterparts ( p < 0.05). Professional players performed significantly better in all physical performance measures except CMJ and SJ time to peak force, CMJ RFD and SJ relative peak force. Variables which were predictive of playing standard were: Σ8 skinfolds, CMJ peak velocity and WB6S absolute and relative peak power ( p < 0.05). These findings indicate that the current body of male professional RU players is anthropometrically and physically superior to their amateur counterparts, although not all variables assessed here were predictive of playing standard. Data presented here indicate that Σ8 skinfolds, WB6S absolute and relative power and CMJ peak velocity are predictive of playing standard, whereas other anthropometric and strength and power variables are not.